Effect of Blade Outlet Angle on Unsteady Hydrodynamic Force of Closed-Type Centrifugal Pump with Single Blade - Yasuyuki Nishi; Junichiro Fukutomi (International Journal of Rotating Machinery)
Geometrically, the single-blade centrifugal impeller, commonly used today as a sewage pump, is not axially symmetric. For this reason, the static pressure around the impeller fluctuates greatly when the impeller is rotating, and not only the radial thrust but also the axial thrust shows large fluctuations. Therefore, it is extremely important for the improvement of pump reliability to quantitatively grasp these fluctuating hydrodynamic forces. In this study, we investigated the unsteady hydrodynamic forces in a closed-type centrifugal pump with a single blade for different blade outlet angles using a numerical analysis that takes into account both experiment and the leakage flow. The results clearly showed the effect of the blade outlet angle on that act on the impeller. The root-mean-square value of the fluctuating component of the total radial thrust was roughly the same for whichever impeller at low flow rate, but at high flow rates, the value increased for impellers with larger blade outlet angles. Moreover, when the leakage flow rate increased with increasing static pressure around the impeller, such that the rear and front shroud parts were subject to high pressure, the absolute value of the axial thrust on both these parts increased.